2005
DOI: 10.1176/appi.ajp.162.6.1100
|View full text |Cite
|
Sign up to set email alerts
|

Response to Emotional Stimuli in Boys With Conduct Disorder

Abstract: Although the self-report data supported a deficit in reactivity to explicit fear cues, the psychophysiological data indicated that boys with conduct disorder both with and without a comorbid condition of ADHD are characterized by a generalized deficit in autonomic responsivity in an experimental situation in which children were exposed to complex visual stimuli of unpredictable affective quality. Psychophysiological findings may point to a deficit in associative information processing systems that normally pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
67
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 31 publications
(25 reference statements)
8
67
1
7
Order By: Relevance
“…These findings extend to a number of stimulus conditions, including (a) responding for monetary incentives, (b) viewing escalating conflict scenes among child actors, and (c) viewing both pleasant (pictures of pets or family scenes) and unpleasant (pictures of wounded children and violent scenes) images (e.g., Beauchaine et al, 2001;Herpertz et al, 2005). In the only study in which autonomic reactivity was assessed specifically during distress cues in such a population, Blair (1999) reported lower skin conductance responses to expressive emotional slides (e.g., a person crying) among clinicreferred children with psychopathic tendencies compared with controls.…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…These findings extend to a number of stimulus conditions, including (a) responding for monetary incentives, (b) viewing escalating conflict scenes among child actors, and (c) viewing both pleasant (pictures of pets or family scenes) and unpleasant (pictures of wounded children and violent scenes) images (e.g., Beauchaine et al, 2001;Herpertz et al, 2005). In the only study in which autonomic reactivity was assessed specifically during distress cues in such a population, Blair (1999) reported lower skin conductance responses to expressive emotional slides (e.g., a person crying) among clinicreferred children with psychopathic tendencies compared with controls.…”
mentioning
confidence: 55%
“…There is now a growing body of literature suggesting that children and adolescents with DBDs have difficulties with several domains of empathic responding, including emotional processing and self-appraisals of emotional experiences (de Wied, Goudena, & Matthys, 2005;Douglas & Strayer, 1996;Herpertz et al, 2005;Strand & Nowicki, 1999). However, other components of empathic responding such as displays of sad facial expressions and autonomic reactivity have only begun to receive empirical attention (Blair, 1999;de Wied et al, 2005;Douglas & Strayer, 1996;Herpertz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that there is a biological component to the development of aggression but it is obvious that individual and social factors can affect or otherwise mitigate biological propensity. More recently, Herpertz and colleagues in studying boys with conduct disorder who have co-morbid ADHD found that conduct disorder correlates with lower emotional reactivity and overall lower autonomic arousal (Herpertz et al 2005).…”
Section: Introductionmentioning
confidence: 99%